Analisis Pengakuan Pendapatan Klaim BPJS Kesehatan Di Rumah Sakit Universitas Mataram - Aulia, Linda Aulia; Bambang (Jurnal Riset Mahasiswa Akuntansi, 2025)
This study aims to analyze the revenue recognition process of BPJS Kesehatan claims at Mataram University Hospital, a government work unit applying Government Accounting Standards (SAP) based on the cash toward accrual basis. The research employed a descriptive quantitative approach, using documentation, interviews, and an analysis of claim reports from January 2025. Findings reveal a negative discrepancy of Rp 181,634,816 between the hospital's submitted claims and those approved by BPJS, with 11.9% of total claims still in pending status. Most discrepancies occurred in outpatient services due to coding errors, incomplete documentation, and limitations in the hospital’s information system. While revenue recognition has been carried out in accordance withSAP principles, the implementation faces administrative and technical challenges that impact cash flow and the accuracy of financial reporting. This study recommends strengthening internal verification systems, enhancing human resource capacity, and integrating hospital information systems to ensure a more efficient and accountable claim process, supporting financial sustainability and continuous healthcare service delivery.